Inventarisasi dan Keragaman Jenis Nyamuk di Lingkungan Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Sriwijaya, Indralaya - Choirunnisa Choirunnisa; Yuanita Windusari; Erwin Nofyan (Seminar Nasional Lahan Suboptimal, 2019)
Choirunnisa C, Windusari Y, Nofyan E. 2019. Inventaritation and diversityo mosquito types at the matematic and natural scieces faculty area, Sriwijaya University, Indralaya. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 211-220. Palembang: Unsri Press.Mosquitoes have a beneficial role for the ecosystem, such as food chain and its role is detrimental to its host as a vector. An appropriate morphology identification can be useful to determine the character and number of species to provide an overview of diversity in some areas as an effort in preventing and controlling the distribution of mosquitoes in the areas or geography. This study aims to identify the types of mosquitoes and to determine the distribution pattern or distribution of mosquito species based on adult mosquitos’ morphology in the Faculty of Mathematics and Natural Sciences, Sriwijaya University Campus, Indralaya. This research has conducted from January until March 2019 at the Faculty of Mathematics and Natural Sciences, Sriwijaya University Campus, Indralaya and identification is done at Entomology Laboratory, Baturaja Health Research and Development Center, South Sumatra. The  Human Landing Collection technique is used to catch mosquitoes that land on the collector’s body. The collector is left in an open space for 12 hour  (06.00 pm until 06.00 am) with 40 minutes catch interval and  rest for 10 minute. This research was carried out with several steps, start from sampling, capturing and collecting species, mosquito preservation (pinning), mosquito identification, and data analysis.  The results are presented in table form by analysis of Shannon-Weinner. The results showed there are species such as Armigeres subalbatus,  Aedes albopictus, Mansonia annulata, Anopheles letifer, Culex vishnui, Culex gellidus, Culex quinquefasciatus, and Culex tritaeniorhynchus.  Then the value of diversity (H ') is obtained at each location from the highest to the lowest sequentially from 3,2,4, and 1 location with values of 0.95, 0.90, 0.82, and 0.34 which symbolized as H' < 1, shows that the diversity of species in a community is low.Keywords: characteristic, distribution  pattern, human landing collection, identification, pinning